Dorsomorphin attenuates ABCG2-mediated multidrug resistance in colorectal cancer - Xiao-Peng Li; Xiao-Peng Li; Liang-Qi Cao; Ze-Zhong Yu; Ze-Zhong Yu; Ke He; Peng-Bo Ding; Ji-Sheng Li; Yi-Yao Shan; Yu-Bin Su; Zhong-Min Yuan; Zhi Shi; et al. (Frontiers Media S.A., 2024)
Colorectal cancer is a common malignant tumor with high mortality, for which chemotherapy resistance is one of the main reasons. The high expression of ABCG2 in the cancer cells and expulsion of anticancer drugs directly cause multidrug resistance (MDR). Therefore, the development of new ABCG2 inhibitors that block the active causes of MDR may provide a strategy for the treatment of colorectal cancer. In this study, we find that dorsomorphin (also known as compound C or BML-275) potently inhibits the transporter activity of ABCG2, thereby preserving the chemotherapeutic agents mitoxantrone and doxorubicin to antagonize MDR in ABCG2-overexpressing colorectal cancer cells. Additionally, dorsomorphin does not alter ABCG2 protein expression. The results of molecular docking studies show that dorsomorphin is bound stably to the ABCG2-binding pocket, suggesting that dorsomorphin is a potent ABCG2 inhibitor that attenuates ABCG2-mediated MDR in colorectal cancer.